Pengaruh Influencer Marketing dan Promosi Penjualan terhadap Impulse Buying Produk Perawatan dan Kecantikan di Shopee Mall pada Generasi Z di Kota Surabaya - Puspitasari, Citra Febrianti; Maduwinarti, Ayun; Pratiwi, Ni Made Ida (Research Journal of Social Science and Economics, 2025)
As time progresses, all aspects of life activities have become more practical and easier with the existence of internet technology. One of the aspects referred to is the trade aspect, as evidenced by the emergence of various marketplace (Shopee, Tokopedia, etc.) and being the most strategic economic sector, in which there are many sellers selling goods/services, sometimes even the same types of products are sold, so business competition is unavoidable. Social media is also a place where the economy grows, giving rise to professions influencer and creating a marketing arena for business actors equipped with sales promotions (discounts, coupons, etc.) to create impulse purchases. The object of this research is the product of the Shopee Mall category of care and beauty. The goal is to find out the effect Influencer Marketing (X1) and Sales Promotion (X2) to Impulse Buying (Y). This type of research uses quantitative methods with Multiple Linear Regression Analysis, the population is generation Z of Surabaya City who have purchased care and beauty products through Shopee Mall, focused on the East Surabaya area with a sample size of 100 respondents from the distribution of statements e-quesinoer via Google Forms. The results obtained state that Influencer Marketing and Sales Promotion has a partial and simultaneous effect on Impulse Buying. Testing this hypothesis is proven through the t (partial) test that Influencer Marketing positive and significant effect onImpulse Buying, also Sales Promotion positive and significant effect on Impulse Buying. As well as the F test (simultaneous) with F count 18.616>F table of 3.09 and a significance level of 0.000<0.05. Obtain a determination value (R²) of 0.277 or 27.7%. While the remaining 72.3% is influenced by other factors and variables outside the study, such as variables Hedonic Shopping Value, FOMO, and Shopping Lifestyle. Keywords: Influencer Marketing, Sales Promotion, Impulse Buying